Balloon Breathing Exercise Games as Motor-Cognitive Coordination in Elderly with Dementia - Sulastien, Herni; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
The elderly represents the final stage in the human life process, characterized by various physical, cognitive, and functional limitations that arise due to the degenerative process. According to statistical data from 2022, the proportion of the elderly population increased from 7.57% in 2021 to 10.48% in 2022. One of the most prevalent conditions among the elderly is dementia, which manifests as a progressive decline in memory, cognitive abilities, and the capacity to perform daily activities. Without intervention, dementia symptoms worsen over time, necessitating targeted therapeutic approaches to prevent its progression. Engaging in recreational activities, such as playing games, has been shown to keep the mind active and foster cognitive engagement. This is particularly important for the elderly, especially those at risk of or experiencing mild dementia. The